Transformation Of Customary Law In Resolution Of Common Land Disputes In The Digital Era - Fitri Arianti Saputri (PT. Anagata Sembagi Education, 2026)
Customary land disputes are among the most complex agrarian issues in Indonesia, as they combine the codified state legal system with the fluid, oral, and community-based customary law. This article aims to analyze how the values, institutions, and dispute resolution mechanisms under customary law have transformed with the introduction of digital technology into national land governance, including electronic land certificates, geospatial information systems, online mediation, and e-court platforms. Using normative legal research methods supported by secondary empirical data, this article finds that digitalization offers opportunities in the form of accelerated evidence, transparency of land ownership data, and expanded access to justice for indigenous communities in remote areas. However, it also presents serious challenges in the form of a digital literacy gap, the risk of losing the value of customary deliberation, and the potential for new conflicts due to non-participatory spatial data conversion. This article concludes that digital transformation should ideally not replace customary mechanisms but rather be positioned as a supporting instrument that strengthens the legitimacy and effectiveness of customary land dispute resolution through a hybrid model between customary institutions and the state's digital system